2007
DOI: 10.1021/ja071189i
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Induced Phospholipid Ordering Depends on Surface Pressure

Abstract: The effect of sodium and calcium ions on zwitterionic and anionic phospholipids monolayers is investigated using vibrational sum-frequency generation in conjunction with surface pressure measurements and fluorescence microscopy. Sodium ions only subtly affect the monolayer structure, while the effect of calcium is large and depends strongly on the surface pressure. At low surface pressures (approximately 5 mN/m), the presence on Ca2+ results in the unexpected appearance of ordered domains. For pressures betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
147
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 36 publications
(67 reference statements)
22
147
1
Order By: Relevance
“…8 Briefly, the visible beam ͑VIS͒ ͑800 nm, ϳ30 J / pulse, spectral bandwidth of 25 cm −1 ͒ is overlapped at the sample position with ϳ5 J / pulse, 150 fs infrared ͑IR͒ beam. The IR wavelength is continuously tuned from 3570 to 5110 nm, such that both the O-D and the C-H stretch vibrational region are covered.…”
mentioning
confidence: 99%
“…8 Briefly, the visible beam ͑VIS͒ ͑800 nm, ϳ30 J / pulse, spectral bandwidth of 25 cm −1 ͒ is overlapped at the sample position with ϳ5 J / pulse, 150 fs infrared ͑IR͒ beam. The IR wavelength is continuously tuned from 3570 to 5110 nm, such that both the O-D and the C-H stretch vibrational region are covered.…”
mentioning
confidence: 99%
“…Sovago et al observed that Ca 2þ ions changed the alkyl chain ordering of zwitterionic DPPC and anionic DMPS phospholipids monolayers [93]. The Ca 2þ ions appeared to induce more ordered structure in the monolayers through their adsorption on the negatively charged phosphate groups, which supposedly decreased the Coulomb repulsion between molecules and enhanced condensation of the monolayer.…”
Section: Mixed Langmuir Monolayersmentioning
confidence: 99%
“…Ion adsorption on the lipid membrane surface has been explored through various techniques, including nuclear magnetic resonance [8,9], Langmuir method [10][11][12] microelectrophoresis [13][14][15] and computational methods, such as molecular dynamics simulations [16,17]. In particular, microelectrophoresis can be used to determine membranes surface charge density values.…”
Section: Introductionmentioning
confidence: 99%